2017
DOI: 10.1080/13887890.2017.1369179
|View full text |Cite
|
Sign up to set email alerts
|

Odonata community structure and patterns of land use in the Atewa Range Forest Reserve, Eastern Region (Ghana)

Abstract: Recent studies have indicated that frequent anthropogenic disturbances in tropical developing countries are primary drivers of reduction in community diversity and local extinction of many arthropods, including dragonflies. We assessed the impact of anthropogenic disturbances on odonate assemblages across three different land use types, in a biodiverse nature reserve in Ghana. A total of 37 transects (100 x 10 m) were used to survey odonate species over two seasons and three rivers which pass through agricultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 40 publications
2
19
1
Order By: Relevance
“…Alpha diversity and abundance were slightly higher in the TRC compared to NFS. Other studies have also reported higher abundance and richness of odonates in agricultural land compared to forest areas (Hofhansl & Schneeweihs, 2008;Seidu et al, 2017). However, the differences in alpha diversity parameters between the two communities were statistically non-significant in our study.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…Alpha diversity and abundance were slightly higher in the TRC compared to NFS. Other studies have also reported higher abundance and richness of odonates in agricultural land compared to forest areas (Hofhansl & Schneeweihs, 2008;Seidu et al, 2017). However, the differences in alpha diversity parameters between the two communities were statistically non-significant in our study.…”
Section: Discussioncontrasting
confidence: 86%
“…Orthetrum triangulare in particular is known to be tolerant to disturbances and can be considered as an indicator of habitat alteration (Dow, 2010a). Additionally, most of the species under family Libellulidae are swift fliers, which requires open areas for active thermoregulation to compensate for the energy lost during their flight (Corbet & May, 2008;Seidu et al, 2017). The dominance of Libellulidae in the rice cultivation ecosystem has been reported by many other studies as well (Dwari & Mondal, 2017;Kulkarni & Subramanian, 2013;Rohmare et al, 2016).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Based on the number of species found, in the Anisoptera order, only species from the family Libellulidae were found, whereas in the suborder Zygoptera species from the Coenagrionidae family were more common than other families. Similar to the results of other Odonata community researches, the Odonata community was dominated by species from the family Libellulidae from the suborder Anisoptera and species from the family Coenagrionidae from the suborder Zygoptera (Mapi-ot et al 2013; Dayakrishna and Arya 2015; Siregar and Bakti 2016;Seidu et al 2017;Ilhamdi 2018).…”
Section: Biodiversity Indexsupporting
confidence: 83%